2007
DOI: 10.1038/sj.gene.6364379
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of type 1 diabetes genes on chromosome 21 in a rat beta-cell line and human pancreatic islets

Abstract: We recently finemapped a type 1 diabetes (T1D)-linked region on chromosome 21, indicating that one or more T1D-linked genes exist in this region with 33 annotated genes. In the current study, we have taken a novel approach using transcriptional profiling in predicting and prioritizing the most likely candidate genes influencing beta-cell function in this region. Two arraybased approaches were used, a rat insulinoma cell line (INS-1ab) overexpressing pancreatic duodenum homeobox 1 (pdx-1) and treated with inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Studies within a T1DM-associated linkage region on chromosome 21 have also identified several genes with altered expression following cytokine exposure [71], including carbonyl transferase ( CBR1 ), which functions as a nitrosylated glutathione reductase important for β cell survival during oxidative stress [72], and the E3 ligase protein tetratricopeptide repeat domain 3 ( TTC3 ), which facilitates the ubiquitination and degradation of the survival factor Akt/PKB [73]. …”
Section: Systems-based Approaches To Identify Novel β Cell Related T1mentioning
confidence: 99%
“…Studies within a T1DM-associated linkage region on chromosome 21 have also identified several genes with altered expression following cytokine exposure [71], including carbonyl transferase ( CBR1 ), which functions as a nitrosylated glutathione reductase important for β cell survival during oxidative stress [72], and the E3 ligase protein tetratricopeptide repeat domain 3 ( TTC3 ), which facilitates the ubiquitination and degradation of the survival factor Akt/PKB [73]. …”
Section: Systems-based Approaches To Identify Novel β Cell Related T1mentioning
confidence: 99%
“…None had classical type 1 diabetes–associated HLA-DR risk genotypes (DR1/3, DR11/52, DR4/5, DR2/5, DR6/13, DR4/6, DR4/5, and one donor missing HLA-DR genotype). Islet preparation, cytokine stimulation, including tumor necrosis factor-α (TNF-α; 5,000 units/mL), interferon-γ (IFN-γ; 750 units/mL), and interleukin (IL)-1β (75 units/mL) for 48 h, and RNA extraction have been described previously (7,22,23). …”
Section: Methodsmentioning
confidence: 99%
“…Network- or pathway-based approaches have been used to identify multiple disease genes for various diseases (712). This includes enrichment in predefined pathways by, for example, Kyoto Encyclopedia of Genes and Genomes (KEGG) (13) (http://www.genome.jp) and Gene Ontology (GO) terms (14) (http://www.geneontology.org).…”
mentioning
confidence: 99%
“…From several candidate genes, some evidence was observed for an association of variants of the CBR1 gene to T1D [24]. A later study revealed down-regulation of CBR1 mRNA in human islets following exposure to a mixture of cytokines, modeling the pathogenetic process in the target organ of T1D [134]. This down-regulation by cytokines may be an important mechanism, potentially making -cells more vulnerable toward oxidative stress [133].…”
Section: Significance In Pathological Statesmentioning
confidence: 99%